pengaruh kualitas pelayanan roomboy terhadap kepuasan tamu menginap di daima hotel padang - Annisa Khairani Harahap (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Abstract. The purposlof this studylis to findlout how muchlinfluence the service qualitylof roomboy has on guest satisfaction staying at Daima HoteliPadang. Thisltypelof researchiis quantitativeldescriptive research. Theisampling technique usedlwas incidental technique with 97 people as samples. Data collection techniques are carried out by distributing questionnaires using a Likert scale. The resultspshowed that: (1) Roomboy's Service Quality was in the good category (40.21%) (2) Guest Satisfaction Staying at Daima Padang Hotel was in the satisfied category (57.73%), (3) Linear regression hypothesis test results simple obtained F 17,388 with the value of sig.l0,000l<0,05, with a R squarel value ofl0,155. This means that roomboy service quality variables have an effect of 15.5% on guest satisfaction deserving at Daima Hotel Padang and 84.5% influenced by other factors. Key words: Guests Satisfaction, Service Quality, Hotel